Qualidade de vida: percepção dos funcionários da Faculdade Independente do Nordeste FAINOR - Brito, ítalo Silva (2014)
This study investigates aspects of quality of life at work that impacts on decision-making and actions that promote a healthy environment and corrective actions to improve the competitiveness of the organizations. It evaluates the perception of the employees of the Faculty Northeast Independent - FAINOR - about the quality of work life. From a methodological point of view, the research was guided by the qualitative approach and the use of the platform World Health Organization Quality of Life (WHOQOL) established by the World Health Organization - WHO. The sample consisted of workers of three different levels: operational, managerial and tacit. The results revealed that the subjects investigated confers to the quality of work life a fundamental importance to achieve goals and targets outlined. In addition, we sought to understand that the assessment of quality in work is fundamental to outline strategies to address problems facing mobility, psychological aspects such as self-esteem, self-image, social relations and also those related to tiredness, fatigue and lack of sleep. It is shown that the environment was the item less prominent, although it also contributes to the acquisition of industrial diseases.